Bioremoval of Mercury )Hg+2(, Copper )Cu+2(, and Lead )Pb+2( from Water by macroalgae; Enteromorpha intestinales - Gammal, Mostafa Abdel Mohsen El; Nageeb, Mohammed; Mubark, Abduljalil Ahmed Al-Shaikh (International Journal of Scientific Research in Biological Sciences, 2020)
Bioremoval is an economically and successful technique to take away heavy metals by macroalgae. Enteromorpha intestinales is one of the main species of green macroalgae in the water Arabian Gulf, Saudi Arabia. It is tested as bioremoving for the three heavy metals; Hg, Cu, and Pb from water. The concentrations solutions of heavy metals have been used in five replicates; Cu (2,4,6,8,10) ppm, Hg (1,2,4,6,8) ppm, and Pb (0.5,1,1.5) ppm with live E. intestinalis. The results were demonstrated that the relative growth was little affected in the three heavy metals concentrations. The removal % and the sorption capacity were more significant with Hg and Cu and lower with Pb. The concentration of heavy metals in dry E. intestinalis was increased with increased concentration of metals in solutions. The bioconcentration; BCF was taken a decreased trend with increased metals. From this study, we can use E. intestinalis for removing the Hg Cu and pb at low concentrations in water pollution.